A serial mediating effect of perceived family support on psychological well-being - An, Jing; Zhu, Xuanyu; Shi, Zhan; An, Jinlong (BMC public health, 2024)
Family has a significant impact on individual mental health. Based on social support theory, family system theory and the Mental Health Continuum Short Form (MHC-SF), this research constructed a model of the pathway of perceived family support on psychological well-being and the results empirically clarified that perceived family support has a significant positive relationship with emotional well-being, social well-being, and psychological well-being ( P < 0.001). Emotional well-being positively influences social well-being and psychological well-being ( P < 0.001). Social well-being positively affects psychological well-being ( P < 0.001). There were direct mediating effects of emotional well-being (13.45%), direct mediating effects of social well-being (32.82%) and a serial mediating effect (28.07%) between perceived family support and psychological well-being ( P < 0.001).